Spiritual Care in Advanced Dementia from the Perspective of Health Providers: A Qualitative Systematic Review - Lucía Rocío Camacho-Montaño; Jorge Pérez-Corrales; Marta Pérez-de-Heredia-Torres; Ana María Martin-Pérez; Javier Güeita-Rodríguez; Juan Francisco Velarde-García; Domingo Palacios-Ceña (Occupational Therapy International)
Background. Worldwide, 47 million people suffer from dementia. Despite recognizing the importance of spirituality within dementia care, it is still unclear how this should be integrated into dementia services. Aim. To explore the perspective of health professionals regarding the spiritual care of people with advanced dementia. Methods. A qualitative systematic review was performed following the Enhancing Transparency in Reporting the Synthesis of Qualitative Research guidelines for the study design. The inclusion criteria included original articles published from January 2008 to March 2019, using either qualitative or mixed methods. The quality of the articles included was evaluated using the consolidated criteria for reporting qualitative research, Standards for Reporting Qualitative Research, and the Critical Appraisal Skills Programme. Synthesis of findings was performed using thematic analysis. Results. Twelve studies were included in the review. Seventeen categories were identified, grouped into four themes: (1) the perception of spirituality, including the failure to address the same, (2) the spiritual needs of people with advanced dementia, (3) spiritual needs from health care providers, and (4) addressing spirituality, with the following categories: music, significant activities, among others. Conclusions. Spirituality is not formally addressed in this population, and professionals do not feel confident enough to be able to integrate spirituality in their care. It is necessary to identify and record the spiritual needs of people with advanced dementia, as well as to design specific care programs.